Benefits and Costs to Community-Based Physicians Teaching Primary Care to Medical Students - Grayson, Martha S (Blackwell Science Inc, 1998)
The purpose of this study was to determine the benefits and costs to community-based primary care physicians teaching medical students in their offices. Survey data were collected from 185 preceptors between 1990 and 1996. Respondents reported increases in their enjoyment of the practice of medicine (82%), time spent reviewing clinical medicine (66%), desire to keep up with recent developments in medicine (49%), and patients' perception of their stature (44%). However, 61% reported a decrease in the number of patients seen when a student was present. We conclude that despite the costs associated with teaching medical students in their offices, preceptors derived many benefits.